2020
DOI: 10.1183/13993003.01616-2020
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial thermoplasty in patients with dynamic hyperinflation: results from the proof-of-concept HEAT trial

Abstract: Severe refractory asthma affects 3-5% of asthmatic patients, but represents 50-80% of asthma-related healthcare costs [1]. Although therapies targeting IgE and, more recently, IL5 and IL4/13 have recently gained approval for the treatment of severe refractory asthma in a subset of patients with type 2 phenotypes, there is still a need to cover a wider range of patients, in particular those with a non-type 2 phenotype or for whom biotherapies failed.Bronchial thermoplasty, a bronchoscopic approach that uses rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, no significant effect had been observed on small airways evaluated by oscillometry 6 months after the procedure, despite significantly improved clinical markers 116. Interestingly, a proof-of-concept pilot study found that bronchial thermoplasty could nevertheless improve dynamic hyperinflation in selected patients 117. Though, such results need to be confirmed in larger and control clinical studies.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, no significant effect had been observed on small airways evaluated by oscillometry 6 months after the procedure, despite significantly improved clinical markers 116. Interestingly, a proof-of-concept pilot study found that bronchial thermoplasty could nevertheless improve dynamic hyperinflation in selected patients 117. Though, such results need to be confirmed in larger and control clinical studies.…”
Section: Introductionmentioning
confidence: 92%
“…116 Interestingly, a proof-of-concept pilot study found that bronchial thermoplasty could nevertheless improve dynamic hyperinflation in selected patients. 117 Though, such results need to be confirmed in larger and control clinical studies.…”
Section: Bronchial Thermoplastymentioning
confidence: 97%
“…• Perform additional economic analyses on a larger scale using real-world data Limited, although increasing, understanding of the role of specific asthma endotypes/phenotypes 55 • Perform additional studies on a larger scale to include extremes of ages, all endotypes/ phenotypes and clinical variants such as cough-variant and exercise-induced asthma 58 Difficulties with insurance coverage even when patients meet the conventional treatment criteria 59 • Relevant professional societies should formulate updated evidence-based clinical practice guidelines to reflect the changing landscape of clinical evidence over the past few years since older guidelines had come out • Engage with insurance companies to educate them about our updated understanding of BT, including its safety, effectiveness and cost-effectiveness Absence of direct comparison with novel biologic therapies 60…”
Section: Current Challenges and Potential Next Stepsmentioning
confidence: 99%